2008
DOI: 10.1002/cne.21746
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 is expressed in mouse multipotent retinal progenitor cells and functions in Müller Glial cell development

Abstract: It is widely accepted that the process of retinal cell fate determination is under tight transcriptional control mediated by a combinatorial code of transcription factors. However, the exact repertoire of factors necessary for the genesis of each retinal cell type remains to be fully defined. Here we show that the HMG-box transcription factor, Sox9, is expressed in multipotent mouse retinal progenitor cells throughout retinogenesis. We also find that Sox9 is downregulated in differentiating neuronal population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
103
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 68 publications
7
103
0
Order By: Relevance
“…Paired SOX Site Contributes to BEST1 Promoter Activity-Of the three SOX-E factors, it was reported that SOX9 is expressed in mouse RPE from embryonic stages through adults (19), raising the possibility that SOX9 might be the regulator of BEST1 in the RPE. Based on the reported findings that SOX9 regulates mouse Col11a2 and Ptgds through paired SOX sites (underlined) CACAAGGCGTGCTTTGTC in the enhancer (41) and CACAAATGGTGCTTTGTG in the promoter (46), respectively, we reanalyzed the sequence of Bait 6.…”
Section: Yoh Screen With Best1 Promoter Elements Identified Sox-ementioning
confidence: 99%
See 4 more Smart Citations
“…Paired SOX Site Contributes to BEST1 Promoter Activity-Of the three SOX-E factors, it was reported that SOX9 is expressed in mouse RPE from embryonic stages through adults (19), raising the possibility that SOX9 might be the regulator of BEST1 in the RPE. Based on the reported findings that SOX9 regulates mouse Col11a2 and Ptgds through paired SOX sites (underlined) CACAAGGCGTGCTTTGTC in the enhancer (41) and CACAAATGGTGCTTTGTG in the promoter (46), respectively, we reanalyzed the sequence of Bait 6.…”
Section: Yoh Screen With Best1 Promoter Elements Identified Sox-ementioning
confidence: 99%
“…2C). As for the antibodies used, the specificity of the AB5535 antibody was previously demonstrated by immunohistochemistry of retinal sections in which SOX9 staining in Müller glia was abrogated in conditional Sox9 knock-out mice (19). The sc-17342 and ab25978 antibodies were both polyclonal and generated using human SOX10 peptides of 20 (N-terminal) and 50 (at 178 -227 amino acid position) amino acids, respectively (63,64).…”
Section: Sox9 Is Highly and Preferentially Expressed In Rpe-mentioning
confidence: 99%
See 3 more Smart Citations